Ressonâncias planetárias spin-órbita com perturbação de terceiro corpo - Ribeiro, Filipe Batista [UNESP] (2015)
In this work we study the dynamics rotation of exoplanets disturbed by a third body. Emphasis will be placed on exoplanets with physical parameters (e.g. radius and mass) consistent with Earth's. In the first step the rotation of the exoplanet is disturbed only by the torque of the central star. Then the model is extended to include the gravitational influence of a companion. We numerically explore the problem using surface of sections, spectral analysis and dynamic maps for several initial conditions. We show that, depending on the initial conditions and parameters of the planetary system, the planet's rotation can be irregular due to the disturbance of the third body. In particular, the Super-Earth Kepler-11b can have its rotation in 1 : 1 spin-orbit resonance, stable in the problem of two bodies, highly disturbed by the planet Kepler- 11c due to orbital configuration close to the 5 : 4 mean motion resonance. We will also show an introduction of dissipative effects in the exoplanet's rotation induced by tides, applied to the planets Kepler-10b and Corot-7b. Finally we calculate the capture probability in the spin-orbit resonance 3 : 2 to Mercury